Creep response in shear of clayey geo-materials under saturated and unsaturated conditions - Mohd Nazer Nor Shahidah; Tarantino Alessandro (E3S Web of Conferences, 2016)
Translational slides in clays are often characterized by long-lasting intermittent movements associated with the fluctuations of pore-water pressure. Physically-based models designed to support hazard analysis of landslide movements and early warning systems require the integration of time-dependent (viscous) constitutive models for the shear displacements because landslide movements are typically controlled by the viscous behaviour of the clay geo-material. This paper presents an investigation of the viscous response of a clay geo-material under saturated and unsaturated conditions. Creep and relaxation tests have been first carried out on saturated clay samples by means of direct shear box. To gain a conceptual understanding of the viscous response of the clay in shear, mechanical analogues were considered based on combinations of springs and dashpots. Preliminary tests on unsaturated samples were finally carried out to gain a first insight into the viscous response of the clay under unsaturated conditions.